Power release in a subcritical reactor - Demchenko, P.O.; Gussev, Ye.V.; Nikolaichuk, L.I. (Вопросы атомной науки и техники, 2005)
Numerical simulation results of power release in a subcritical reactor in which the neutron field is generated
under bombardment of an actinide target by a relativistic proton beam are given. Представлено результати чисельного моделювання енерговиділення в підкритичному реакторі,
нейтронне поле в якому генерується пучком релятивістських протонів при бомбардуванні мішені з
актинідів. Приведены результаты численного моделирования энерговыделения в подкритическом реакторе,
нейтронное поле в котором генерируется пучком релятивистских протонов при бомбардировке мишени из
актинидов.